Non-destructive evaluation of bondline defects in honeycomb composite - Phua, Jia Po (2019)
The non-destructive testing in this report focuses on disbond detection in a thin composite honeycomb sandwich structure plate. Several types of ultrasonic inspection and bond testing methods are presented in this report. The methods are described in detail individually. Comparisons are made between each type of ultrasonic inspection used and the sensitivity of each method. Next, using ABAQUS software, a finite element analysis of a multi-layered thin composite honeycomb sandwich structure plate with disbonds was carried out, in order to better understand the wave propagation and visualization of wave interaction at the defect.